A theory of simplicity in games and mechanism design - Marek Pycia; Peter Troyan (University of Zurich, Department of Economics, 2021)
We introduce a general class of simplicity standards that vary the foresight abilities required of agents in extensive-form games. Rather than planning for the entire future of a game, agents are presumed to be able to plan only for those histories they view as simple from their current perspective. Agents may update their so-called strategic plan as the game progresses, and, at any point, for the called-for action to be simply dominant, it must lead to unambiguously better outcomes, no matter what occurs at non-simple histories. We use our gradated approach to simplicity to provide characterizations of simple mechanisms. While more demanding simplicity standards may reduce the flexibility of the designer in some cases, this is not always true, and many well-known mechanisms are simple, including ascending auctions, posted prices, and serial dictatorship-style mechanisms. In particular, we explain the widespread popularity of the well-known Random Priority mechanism by characterizing it as the unique mechanism that is efficient, fair, and simple to play.
Keywords: C72; C78; D01; D02; D44; D47; D82; 330; Simplicity; simple dominance; limited foresight; obvious dominance; strongly obvious dominance; market design; mechanism design; extensive-form games; auctions; allocation